The Contemporary Significance Of Fakriddin Rozi And “Mafotihul Ghaib” (Wire Insights: Journal of Innovation Insights, 2024)
the article focuses on the life and work of the famous Mufassir Fakhriddin Raza and his famous book “Mafatihul Gaiba”